Body Composition and Macronutrient Intake are Correlated with Physical Fitness of Basketball Student-Athlete - Muhammad, Rafly Yusuf; Pratama, Satwika Arya; Wahjuni, Endang Sri; Mayasari, Noor Rohmah; Dini, Cleonara Yanuar (Journal of Sport and Exercise Science, 2025)
Purpose: This study aims to investigate the correlation between body composition and macronutrient intake on the physical fitness of basketball student-athletes. Physical fitness is essential for basketball athletes, enabling them to engage in training and competition effectively and efficiently. Several factors influence physical fitness, including body composition and nutrient intake. Body composition significantly impacts the performance of basketball athletes, with anthropometric measurements affecting hand grip strength crucial for ball handling and throwing. Optimal nutrient intake is essential for maximizing athletic performance. Student-athletes have not reached the pro level in terms of nutrition knowledge, quantity and intensity of the match, and economic aspects. Materials and Methods: This is a quantitative study with a cross-sectional design. Participants included 32 male and 16 female basketball student-athletes aged 19-22. Body composition (fat and muscle percentage) was measured using Bioelectrical Impedance Analysis (BIA) Omron Karada Scan HBF-375, macronutrient intake (energy, protein, fat, and carbohydrate) was assessed using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and physical fitness was evaluated using the Multi-Stage Fitness Test (MFT). The correlation between variables was analyzed using Pearson and Spearman correlation tests. Result: The findings revealed a significant correlation between body fat percentage (p = 0.001; r = -.477*), subcutaneous fat (p = 0.000; r = -.622), and muscle mass (p = 0.000; r = .739) with physical fitness. Additionally, a significant correlation was found between energy intake (p = 0.002; r = .436), protein intake (p = 0.000; r = .518*), and fat intake (p = 0.001; r = .446) and physical fitness. However, carbohydrate intake (p = 0.117; r = .229) showed no significant correlation with physical fitness. Conclusion: This study concludes that body composition, specifically fat percentage and muscle mass, has a significant correlation on physical fitness. Energy, protein, and fat intake are significantly correlated to physical fitness, while carbohydrate intake does not demonstrate a significant correlation.